Effects of protein malnutrition on glucose tolerance in rats with alloxan-induced diabetes - De-Mello, M. A R [UNESP]; Luciano, E. [UNESP] (My University, 1995)
Protein-calorie malnutrition produces glucose intolerance and reduced insulin release in response to glucose. Rats adapted to low- or high-protein diets show an increased resistance to the diabetogenic action of a single dose of streptozotocin or alloxan. To determine the effects of dietary protein level on pancreatic function, we measured serum glucose levels under basal conditions and during the oral glucose tolerance test (GTT) performed before and after a single dose of alloxan administered to rats fed a 25% or a 6% protein diet for a period of 8 weeks. The incidence of mild hyperglycemia (serum glucose > 250 mg/dl) was greater among the rats fed the 25% protein diet (81%) than among those fed the 6% protein diet (42%). During the GTT performed before alloxan administration the serum glucose levels of the rats fed the 6% protein diet were not found to be significantly different from those of rats fed the 25% protein diet. During the GTT performed after alloxan injection all rats showed intolerance to the substrate (serum glucose > 160 mg/dl 120 min after glucose administration) regardless of whether basal serum glucose was normal or high. In summary, alloxan was less effective in producing basal hyperglycemia in the rats fed the 6% protein diet than in those fed the 25% protein diet but caused glucose intolerance during the oral GTT in both groups. Thus, it seems that feeding a 6% protein diet to rats offers only partial protection against the toxic effects of alloxan.
Keywords: alloxan diabetes; glucose tolerance test; pancreatic function; protein malnutrition; alloxan; glucose; protein; alloxan diabetes mellitus; animal experiment; animal model; controlled study; diabetes mellitus; glucose blood level; glucose tolerance; hyperglycemia; intravenous drug administration; male; nonhuman; pancreas function; rat; short survey; Animal; Blood Glucose; Diabetes Mellitus, Experimental; Dietary Proteins; Glucose Tolerance Test; Hyperglycemia; Male; Protein-Energy Malnutrition; Rats; Rats, Wistar; Support, Non-U.S. Gov't